Transfer Pricing dari Perspektif Perencanaan Pajak, Thin Capitalization, dan Ukuran Perusahaan - Vasini, Ni Nyoman Nikunja; Kusbandiyah, Ani; Fakhruddin, Iwan; Hapsari, Ira (E-Jurnal Akuntansi; Vol 34 No 3 (2024)DO - 10.24843/EJA.2024.v34.i03.p16, 2024)
The research aims to obtain empirical evidence regarding the influence of tax planning, thin capitalization and firm size on transfer pricing decisions. The sample in this research is unbalanced panel data of 30 coal sector companies listed on the Indonesia Stock Exchange (BEI) for the 2015-2022 period. A total of 141 observation data met the criteria selected using purposive sampling. The results of this research using panel data regression show that tax planning and firm size have a positive effect on transfer pricing decisions, but thin capitalization has no effect on transfer pricing decisions. Keywords: Related parties; Coal; Tax; Subsidiaries